Enalapril inhibits inflammatory osteolysis induced by wear debris in a mouse model. Issue 6 (June 2020) - Ma, Huanzhi; Zhang, Qin; Shi, Jun; Gao, Yutong; Sun, Chengliang; Zhang, Wei
Objective: Aseptic loosening, the most frequent complication after total joint replacement, is probably caused by an inflammatory response to the shedding of wear debris from the implant. The only effective treatment is surgical revision. Using a mouse model, we investigated whether enalapril inhibits wear debris-induced inflammatory osteolysis. Methods: Titanium (Ti) alloy particles were introduced, and calvarial bone from syngeneic mice was implanted into air pouches established in BALB/c mice. Histological and molecular analyses were performed with inflammatory tissue samples obtained from mice treated with and without enalapril. Results: Enalapril inhibited tissue inflammation and inflammatory osteolysis induced by Ti particles, reducing pouch membrane thickness and decreasing inflammatory cell infiltration. In addition, enalapril inhibited the expression of the inflammatory cytokines vascular endothelial growth factor and tumor necrosis factor-α. Conclusions: Our study provides evidence that enalapril inhibits Ti particle-induced inflammatory osteolysis, and it may be a potentially useful treatment for aseptic loosening.